An Evaluation Instrument (Q-U) for Measuring the usability of Business Intelligence Application - Hameed Mousa, Ayad; Adnan Raheem, Heba; Talib Mohammed, Nibras (International Journal of Engineering and Technology, 2018)
The main purpose of Business Intelligence (BI) applications is to focus on supporting organizations' strategic, operational and tactical decisions by providing comprehensive, accurate and vivid data to the decision makers. Usability testing is an important part of software development. It focuses on how well users can understand and utilize a product/software in fulfilling their intended goals. In the software development, most software tends to be complex. Hence, the way to ensure that such software will satisfy users will be done by measuring the usability of such software. Due to using many data integration techniques in developing BI application, thus, the different software have different instruments to measure the usability of BI software. In this paper, the new instrument (Q-U) for measuring BI software was developed. A systematic approach was adopted which suggested by many researchers in developing the intended Q-U instrument.The literature has been reviewed in a systematic manner to elicitation Q-U instrument attributes. Multi-methods were used in validating Q-U instrument such as face validity, a pilot study for testing the goodness ofÂ Â Q-U consistency, and factor analysis. Multi-methods were used in validating Q-U instrument such as face validity, a pilot study for testing the goodness ofÂ Â Q-U consistency, and factor analysis as well as Bartlettâ€™s test for measuring the reliability of Q_U. The finding obtained indicates the workability of Q_U in measuring the usability OF BI applications. Ultimately, Q_U was used in measuring BI application in two different sectors.Â Â